Graphene-modified g-C3N4/ α-Fe2O3 systems for light-induced hydrogen generation - Wassila Touati; Miroslava Filip Edelmannová; Mohamed Karmaoui; Ahmed Bekka; Clarisse Furgeaud; Chakib Alaoui; Imene kadi Allah; Bruno Figueiredo; J.A. Labrincha; Raul Arenal; Kamila Koci; David Maria Tobaldi (Carbon Trends)
Photocatalysis represents an advanced and efficient technology for harnessing light energy. The non-toxicity, affordability, and versatility of this technique render it particularly attractive for hydrogen production via water splitting. Nevertheless, the primary challenge lies in identifying materials capable of efficiently catalyzing the water splitting reaction upon exposure to light. This study presents the influence of the quantity of hematite and graphene on g-C3N4 in the context of hydrogen generation from methanol-water decomposition under UVC irradiation. Pure g-C3N4 exhibits the highest hydrogen generation efficiency. However, adding hematite decreases photocatalytic efficiency, likely due to the formation of a type II heterojunction between α-Fe2O3 and g-C3N4, which reduces the overall reduction capacity of the system. While incorporating graphene into the g-C3N4/α-Fe2O3 system enhances photocatalytic efficiency by improving electron mobility and prolonging the lifetime of photo-generated excitons, the highest yield was achieved with BUF10/GNP0.5. This research offers valuable insights into charge transfer and separation processes for photo-generated excitons within the g-C3N4/α-Fe2O3 and g-C3N4/α-Fe2O3/graphene systems in the context of light-induced hydrogen production.